1. The problem statement, all variables and given/known data Attached file shows the problem statement. 3. The attempt at a solution I can do this problem easily. Problem is that there's just one step in my book's derivation that I don't understand. It sets ρ equal to the hypotenuse in the triangle and then says that: dl = ρ/sinθ dθ (1) For some reason I can't get this result. If we look at the cosine of θ then: cosθ = l/ρ => l = ρcosθ => dl/dθ = -ρsinθ =>dl = -ρsinθdθ Incosistent with (1). What am I doing wrong?